(untitled) (Bioscience Journal, 2014)
A field trial was conducted designed in a completely randomized block in a 4 x 3 factorial arrangement to evaluate the application of nitrogen doses (N) (0, 40, 80 and 160 kg/ha) on the morphogenical characteristics and dry matter partition of three forage grasses (Panicum maximum cvs. Mombasa and Tanzania and Brachiaria sp. Hybrid Mulato). The leaf appearance (LAR, leaf/day) and stretching (LER; mm/day) rates, the number of green leaves per tiller (NLT) and the average weight of tillers (MTW; g) presented s positive linear response to the N dose while the phyllochron (Phil; day/leaves) showed a negative linear response. The highest LER, IAL and final leaf length (FLL; cm) occurred in the Mombaça and Tanzania grasses, while the highest LAR occurred in the Mulato grass. There was a negative quadratic effect of the N dose on the stem elongation rate (SER; mm/day) and LF. The Mombaça and Tanzania grasses presented the highest SER; however, in just two forages. The production of total dry matter (TDM; kg/ha), leaves (LDM; kg/ha) and stems (SDM; kg/ha) increased linearly and quadratically with the N dose, respectively, for the Mombaça and Tanzania grasses. There was a high positive correlation among DM, LDM and SDM and the Mombaça grass MTW. The dry matter production and morphogenic characteristics were influenced by the nitrogen fertilization as a result of the substantial increase in the flow of tissues stimulated by fertilization, proving the importance of N for forage biomass accumulation.